Pengaruh Financial Distress, Opini Audit, Dan Price Earning Ratio Terhadap Harga Saham - Wong, Vanessa; Desyana, Gita; Ikhsan, Syarbini (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
Covid-19 pandemic, which occured in Indonesia during the year 2020 and continued with the emergence of Omicron variant in 2022, has caused a tremendously negative impact on the stock market, causing a downhill in stock prices almost across all industries, even resulting in financial failure for some companies, including bankruptcy. As the pandemic gradually subsided and concerns over Omicron faded, stock prices began a steady and significant recovery. This research focused on analyzing the effect of Financial Distress, Audit Opinion, and Price Earning Ratio (PER) on stock prices of restaurant, hotel, and tourism firms listed on the Indonesian Stock Exchange. The source material used is secondary data, namely the company's financial statements published on the Indonesian Stock Exchange website in 2021-2023. Purposive sampling method was used to gather the sample and underwent further analysis by a multiple regression technique. The analysis revealed that financial distress and audit opinion had an impact on stock prices. Meanwhile, the price earning ratio caused no change in stock prices.